Good Woman, Bad Woman: Language, Gender and Agency in Pakistani TV Dramas - Asif, Dania; Ahmad, Mahboob (Annals of Human and Social Sciences, 2023)
The present study analyses Pakistani TV dramas to explore the relationship between language and gender in a postcolonial society. The binary logic of state hatred against English as a former coloniser’s language dictates that the question of language becomes even more complicated when it interacts with the larger question of gender in a postcolonial state like Pakistan. This can be witnessed in contemporary TV dramas in the country. This paper looks at two such dramas to contend that English language in these dramas is associated with the “bad woman” and Urdu with the “good woman.” The study uses textual analysis for the analysis of Pakistani TV dramas Humsafar (2011) and Zindagi Gulzar Hai (2012). The study concludes that there is a causal relationship between the perception of women as “good” or “bad” and their use of language in these dramas.